Lifestyle and fertility: the influence of stress and quality of life on male fertility. Issue 1 (December 2018) - Ilacqua, Alessandro; Izzo, Giulia; Emerenziani, Gian; Baldari, Carlo; Aversa, Antonio
Abstract Background Male infertility is a widespread condition among couples. In about 50% of cases, couple infertility is attributable to the male partner, mainly due to a failure in spermatogenesis. In recent times, the crucial role that modifiable lifestyle factors play in the development of infertility have generated a growing interest in this field of study, i.e. aging, psychological stress, nutrition, physical activity, caffeine, high scrotal temperature, hot water, mobile telephone use. Several studies have investigated associations between semen quality and the presence of lifestyle stressors i.e. occupational, life events (war, earthquake, etc.) or couple infertility; overall, these studies provide evidence that semen quality is impaired by psychological stress. In this review, we will discuss the impact of quality of life (modifiable lifestyle factors) and psychological stress on male fertility. In addition, the role that increased scrotal temperature along with inappropriate nutritional and physical exercise attitudes exert on male fertility will be presented. Conclusion The decline of male fertility, particularly associated with advancing age, incorrect lifestyles and environmental factors plays an important role on natality, and its consequences on the future on human population makes this an important public health issue in this century. Thus, modification of lifestyle through a structured program of educational, environmental, nutritional/physical exercise and psychological support, combined with the use of nutraceutical antioxidants can prevent infertility and therefore, may help couples to obtain better quality of life and improved possibility to conceive spontaneously or optimize their chances of conception.